2015
DOI: 10.3390/md13041666
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Lipophilic Marine Toxins in Shellfish from Galicia (NW of Spain) and Synergies among Them

Abstract: Lipophilic marine toxins pose a serious threat for consumers and an enormous economic problem for shellfish producers. Synergistic interaction among toxins may play an important role in the toxicity of shellfish and consequently in human intoxications. In order to study the toxic profile of molluscs, sampled during toxic episodes occurring in different locations in Galicia in 2014, shellfish were analyzed by liquid chromatography tandem mass spectrometry (LC–MS/MS), the official method for the detection of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…These data confirm the observation reported from oral exposure of mice where no combined toxic effect was detected after repeated oral doses of 1 mg/kg YTX and 0.185 mg/kg of OA in comparison with individual toxins [ 23 ]. Similarly, Rodriguez et al (2015) [ 46 ] studied recently the toxicity of OA (1–500 nM) in combination with 500 nM YTX on human neuroblastoma cells but did not observed any evidence of synergism after 24 h of exposure although an increased toxicity was detected after 48 h of exposure. Therefore, we suggest that further investigations with a longer incubation time should be performed using our method as a longer treatment time could modify interactions and might induce different pathways.…”
Section: Discussionmentioning
confidence: 98%
“…These data confirm the observation reported from oral exposure of mice where no combined toxic effect was detected after repeated oral doses of 1 mg/kg YTX and 0.185 mg/kg of OA in comparison with individual toxins [ 23 ]. Similarly, Rodriguez et al (2015) [ 46 ] studied recently the toxicity of OA (1–500 nM) in combination with 500 nM YTX on human neuroblastoma cells but did not observed any evidence of synergism after 24 h of exposure although an increased toxicity was detected after 48 h of exposure. Therefore, we suggest that further investigations with a longer incubation time should be performed using our method as a longer treatment time could modify interactions and might induce different pathways.…”
Section: Discussionmentioning
confidence: 98%
“…The phytoplankton responsible for LMTs include Prorocentrum lima , a range of Dinophysis species, Gymnodinium , Azadinium poporum and Karenia brevis [ 14 , 15 ]. The distribution and frequency of occurrence of LMT-producing microalgae have increased throughout the world in recent decades [ 8 , 9 , 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In China, there have been reports of the aforementioned algae species and episodes of LMT accumulation in shellfish along the coasts of Liaoning, Shandong, Zhejiang, Fujian, and Guangdong provinces [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…García-Mendoza et al 2014detected OA, PTX2 and dinophysistoxins (reaching 1647 μg.kg−1) in cultivated mussels (Mytilus galloprovincialis) from Baja California, Mexico. In Europe, on the Galician coast, Rodríguez et al (2015) found that toxin profiles of studied mollusks comprised of OA and YTX. YTXs in mussels.…”
Section: Resultsmentioning
confidence: 97%
“…Some groups of toxins are known to cause human sickness after being consumed (European Food Safety Authority (EFSA), 2008a;EFSA, 2008bEFSA, 2009. The toxicological information for YTXs includes mainly studies on their acute toxicity in mice (Rodríguez et al 2015). YTXs are potent cytotoxins (Paz et al 2007), able to cause damage of the myocardium (Aune et al 2003;Tubaro et al 2004).…”
Section: Introductionmentioning
confidence: 99%